2016
DOI: 10.1002/pola.28391
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of diarylethylene‐based polymeric semiconductors for high‐performance organic field‐effect transistors

Abstract: Constructing planar, rigid, and high electronically delocalized p-conjugated molecular system is the most basic requirements of obtaining high-performance polymeric semiconductors for organic field-effect transistors (OFETs). In this regard, diarylethylene (DAE)-based polymers show great potential because many substantive progresses related to polymer field-effect transistors had been achieved from the kind of polymer materials in recent years. In the brief review, series of DAE-based polymer are highlighted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 137 publications
(171 reference statements)
0
14
0
Order By: Relevance
“…The charge carrier mobility of polymers with trans -vinylene and thiophene-derived repeating units ( trans -poly­(thienylenevinylene)­s; PTVs) has been reported to be the highest among π-conjugated polymers. However, trans -PTVs have strong interchain π–π interactions due to their planar structure, which limits their solubility. , The more twisted configuration of the cis -vinylene units tends to result in less optimized interchain stacking and thus higher solubility . We have demonstrated that thin films of cis -poly­( p -phenylenevinylene)­s undergo cis-to-trans isomerization under UV irradiation (Figure e). A similar isomerization of cis -vinylene may provide a direct and efficient route to the fabrication of trans -PTVs thin films (Figure f).…”
Section: Introductionmentioning
confidence: 98%
“…The charge carrier mobility of polymers with trans -vinylene and thiophene-derived repeating units ( trans -poly­(thienylenevinylene)­s; PTVs) has been reported to be the highest among π-conjugated polymers. However, trans -PTVs have strong interchain π–π interactions due to their planar structure, which limits their solubility. , The more twisted configuration of the cis -vinylene units tends to result in less optimized interchain stacking and thus higher solubility . We have demonstrated that thin films of cis -poly­( p -phenylenevinylene)­s undergo cis-to-trans isomerization under UV irradiation (Figure e). A similar isomerization of cis -vinylene may provide a direct and efficient route to the fabrication of trans -PTVs thin films (Figure f).…”
Section: Introductionmentioning
confidence: 98%
“…In 2011, Grimsdale and co-workers substituted one of the S atoms in BBT by an N atom, allowing the introduction of a solubilizing alkyl chain and producing a new acceptor unit, [1,2,5]­thiadiazolo­[3,4- f ]­benzo­[1,2,3]­triazole (TBZ) . Since then, TBZ has been used for the design of many D–A conjugated polymers. On the other hand, a variety of donor units have been studied, and it was shown that diarylethylene-based (DAE) donor units are suitable for high mobility polymers . This signifies the importance of the backbone planarity, which enables the formation of close π–π stacking and crystalline grains in thin films. Examples of extensively studied DAE units are dithienyl­ethylene (DTE), diseleno­phenylethylene (DSE), ,, and dithieno­[3,2- b ]­thio­phenylethylene (DTTE). ,,, In particular, DTTE forms a more extended π-conjugated core in the polymer backbone compared to DTE.…”
Section: Introductionmentioning
confidence: 99%
“…36−41 On the other hand, a variety of donor units have been studied, and it was shown that diarylethylene-based (DAE) donor units are suitable for high mobility polymers. 42 This signifies the importance of the backbone planarity, which enables the formation of close π−π stacking and crystalline grains in thin films. 43−45 Examples of extensively studied DAE units are dithienylethylene (DTE), 46−51 diselenophenylethylene (DSE), 9,20,50−52 and dithieno [3,2-b]thiophenylethylene (DTTE).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this study, we examined the synthesis of a D-A polymer with 1,2-dithienylethene (DTE) as donor units; poly( 1 - alt - 2 ) in Scheme 1 . DTE-based D-A polymers, such as poly( 1 - alt - 2 ), have been prepared by Migita–Kosugi–Stille cross-coupling polymerization and have proven to be competent compounds in OFETs [ 21 , 22 , 23 ]; however, their synthesis via DArP has been poorly successful [ 24 ]. This is probably due to the existence of plural C–H bonds in DTE.…”
Section: Introductionmentioning
confidence: 99%